THE FAMILY TRADITIONS OF THE GENS MARCIA BETWEEN THE FOURTH AND THIRD CENTURIES b.c. (May 2021) - Morelli, Davide
Abstract: In the mid fourth century b.c. some Roman gentes drew on a Pythagorean tradition. In this tradition, Numa's role of Pythagoras' disciple connected Rome (and the gentes ) with Greek elites and culture. The Marcii, between 304 and 300 b.c., used Numa's figure, recently reshaped by the Aemilii and the Pinarii for their propaganda, to promote the need for a plebeian pontificate. After the approval of the Ogulnium plebiscite (300 b.c. ), the needs for this kind of propaganda fell away. When Marcius Censorinus became censor, Numa's pontificate was no longer relevant for promoting the gens. For this reason, the Marcii used another genealogy for similar propagandistic effect: the figure of Marsyas, a symbol of plebeian ideals.